Assessment of genetic and epigenetic variations in potato somatic hybrids by Methylation-sensitive ISSR and RAPD markers (Bangladesh Journal of Botany, 2015)
Genetic and epigenetic changes (DNA methylation) in the mother plants of somatic hybrids (1st cycle) and their regenerants (30th cycles sub-cultured) were analyzed using methylation-sensitive ISSR and RAPD markers. ISSR and RAPD profiles and their cluster analyses based on the Jaccards similarity coefficient revealed 100% genetic similarity among the mother plant and their regenerants. While for the epigenetic changes in the samples, the MS-ISSR markers detected DNA methylation (2.7%) in the regenerants compared to the mother plant (1%), whereas MS-RAPD markers detected a little methylation patterns in the regeneratns (0.6%) compared to the mother plants (0.4%). DOI: http://dx.doi.org/10.3329/bjb.v44i1.22722 Bangladesh J. Bot. 44(1): 45-50, 2015 (March)